Using the REC Method to Evaluate the Financial Stability of Indonesian and Malaysian Islamic Banks - Sefti Nur Cahya Putri; Havid Risyanto; Asep Dadan Suganda; En. Muhamad Husni (Economica: Jurnal Ekonomi Islam, 2021)
This research aimed to analyze the health level of Islamic banking both in Indonesia and Malaysia by using the REC approach; Risk Profile, Earning, and Capital. Furthermore, this research used the quantitative descriptive method, with collected data from the official websites such as Bank Indonesia, the Financial Service Authority, and Bank Negara Malaysia. In the determination of the sample, the researchers used a purposive sampling technique with convenience sampling it was 12 Islamic Commercial Banks both in Indonesia and Malaysia. The finding of this research partially through three approaches, namely the risk profile approach which is represented by the FDR ratio, the results show that there are significant differences in the soundness of Islamic banking in Indonesia and Malaysia. Then, through the earning approach represented by the ROA ratio, the results showed that there was no significant difference in the soundness of Islamic banking in Indonesia and Malaysia. Likewise, for the capital approach represented by the CAR ratio, the results show that there is no significant difference in the soundness of Islamic banking in Indonesia and Malaysia. Simultaneously, the REC approach proves that there is no significant difference in the soundness of Islamic banking in Indonesia and Malaysia